2020
DOI: 10.1016/j.eclinm.2020.100458
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the risk-benefit profile of ramucirumab in patients with advanced solid tumors: A meta-analysis of randomized controlled trials

Abstract: Background Ramucirumab is a widely used cancer drug having gained six regulatory approvals in various advanced solid tumors. Thus, assessing the risk-benefit profile of such a commonly used drug across multiple tumor types is necessary to inform clinical and reimbursement decisions. To objectively assess the risks and benefits of ramucirumab in patients with advanced solid tumors, we performed a systematic review and meta-analysis of published randomized controlled trials (RCTs). Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The incidence of adverse events was similar to expectations. Ramucirumab has shown improvement in OS in RCTs on other solid tumors [ 74 ]. Another trial by McHugh et al (2020) has also shown no activity of cixutumumab with temsirolimus [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of adverse events was similar to expectations. Ramucirumab has shown improvement in OS in RCTs on other solid tumors [ 74 ]. Another trial by McHugh et al (2020) has also shown no activity of cixutumumab with temsirolimus [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ramucirumab approval was thereafter expanded to combination treatment with chemotherapy for gastric cancer, non-small cell lung cancer (NSCLC), and colon cancer. The drug is also approved as monotherapy for hepatocellular carcinoma (HCC), and most recently in combination with erlotinib for patients with epidermal growth factor receptor (EGFR)-positive NSCLC (Effing and Gyawali, 2020).…”
Section: Ramucirumabmentioning
confidence: 99%
“…Additionally, since access to bevacizumab is limited in some regions or circumstances, more affordable biosimilars have been developed some of which have already been approved for advanced non-small cell lung cancer and metastatic colorectal cancer (Bevacizumab Updates – Big Molecule Watch) [76] . Other monoclonal antibodies with anti-angiogenic properties include ramucirumab (Cyramza), which targets VEGFR-2 and has been approved for the treatment of metastatic gastric cancer and hepatocellular cancer as monotherapy, and for non-small cell lung cancer, colorectal cancer and gastric cancer in combination with chemotherapy [ 47 , 77 , 78 ].…”
Section: Available Strategies To Target Tumor Hypoxiamentioning
confidence: 99%